ANIMATION VIDEO DEVELOPMENT TO IMPROVE STUDENTS ENGLISH READING ABILITY AT SMP NEGERI 1 STABAT - Frimaulia, Sara (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2025)
This study aims to determine the feasibility and effectiveness of animated videos to improve English reading skills. This study is a research and development (Research and Development) which aims to produce learning media in the form of animated videos that can improve the English reading skills of junior high school students. The development model used is the 4D model, namely define, design, development and dissemination. This study was conducted at SMP Negeri 1 Stabat. The subjects of the study were 32 grade VII students. The object of the study was animated videos. The data collection techniques used were observation, interviews, questionnaires and tests. This study will use analysis techniques, namely (1) analysis of the feasibility of animated videos; (b) analysis of the effectiveness of animated videos. Based on the validation results from material experts, a percentage of 86.78% was obtained which was included in the "feasible" category. While the validation results from media experts showed a higher percentage, namely obtaining a percentage of 94.65% which was included in the "very feasible" category. There has been an increase in the English reading skills of grade VII students at SMP Negeri 1 Stabat. This is proven by the average pretest of 56.6 and the average posttest of 80.6. So the percentage increase is 42.65%. And the average N-gain of students is 0.5535 or 55.35% which is included in the moderate category. This shows that the increase in students' English reading ability after learning is quite significant. Based on the description above, it can be concluded that animated videos to improve English reading ability are feasible and effective for use in SMP Negeri 1 Stabat.